«Curiales» y «cismáticos»: la romanización y la controversia eclesiológica en el Perú (1855-1857). - RUIZ, Rolando IBERICO (Humanidades: Revista de la Universidad de Montevideo, 2022)
The article analyzes the ecclesiological controversy in Peru between the ultramontane Catholic sectors and the liberal-Gallican sectors from 1855 to 1857. The ideological struggle took place in the political context of the liberal revolution and allowed the ultramontanes to promote the institutional and theological Romanization of the Church. However, they encountered resistance from the liberal-Gallican Catholics, whose ideas were based on liberal and Gallican political theories. The article analyzes the political-theological positions regarding the Church and the papacy, and how these changes led to the consolidation of ultramontanism and Romanization in Peru.